Exploring Financial Bootstrapping and Financial Capital Through Financial Literacy to Enhance Micro Business Performance in Madura's Culinary Industry - Purnamawati, Purnamawati; Rachmawati, Eka; Gitayuda, M. Boy Singgih (UMSurabaya Publishing, 2025)
Funding management for culinary micro-enterprises in Madura requires real action, including applying financial literacy indicators, regarding the study of how financial capital and bootstrapping affect micro-enterprises performance in the Madura culinary industry. This study aimed to examine the effect of financial bootstrapping and financial capital through financial literacy on microbusiness performance. The method used in this research is quantitative. The sampling technique used was purposive sampling with research respondents of culinary micro businesses in Madura. The sample obtained was 110 respondents. The data in this study used primary data, namely a questionnaire. The results showed that increasing financial literacy is the key to maximizing resource potential and improving micro-business performance in the Madura culinary sector. In the context of research on the effect of financial bootstrapping and financial capital on the performance of micro-businesses in the culinary industry in Madura, supported by Pecking Order Theory (POT), it provides a relevant framework for understanding the financing decisions taken by business actors. This research provides an overview of empirical support related to good financial literacy's importance in improving financial management and microbusiness performance.